A review on volatilization of flame retarding compounds from polymeric textile materials used in firefighter protective garment. (July 2023) - Mokoana, Vincent N; Asante, Joseph KO; Okonkwo, O Jonathan
Polymeric textile materials, now, find extensive application in modern society than previously imagined, particularly in protective clothing. The application of these polymeric materials has been restricted by their flammability and contribution to fire risk. Flame retarding compounds and inherent flame-retardant materials have been introduced to reduce and even halt the flammability of polymers. However, over time, flame retardants tend to leach out of materials. The exposure of polymer textile to varying heat intensities may trigger polymer and flame retardant's volatilization and thermal degradation. Firefighters may be exposed to toxic chemicals through the volatilization of flame-retardant compounds from the bunker gear. Flame retardant's volatilization is associated with thermal degradation of the flame-retardant chemical compounds in the textile material. This review focuses on volatilization of flame retardants from protective textile materials resulting from exposure to heat and seeks to provide the necessary understanding about the release of flame retardants from flame-retardant textiles, particularly firefighting garments.